2011
DOI: 10.1111/j.1743-6109.2011.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Revision Penile Prosthesis Surgery Is Not Associated with a High Risk of Implant Colonization or Infection: A Single-Surgeon Series

Abstract: Introduction Revision penile prosthesis surgery has traditionally been associated with a greater risk of postoperative infection than primary implant placement. This has been attributed to the high prevalence of asymptomatic bacteria found surrounding the implant at the time of revision surgery. Aim To validate whether contemporary revision surgery remains associated with a high risk of asymptomatic colonization and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…However, the organisms are suppressed by the antibiotics in M/R impregnated devices and must be recognized and cautiously monitored in clinical practice, and assessed in future research. 13,14,18,21,22 To our knowledge the strength of the data used for analysis provides the most tangible evidence to date that M/R impregnated implants are enhanced and require fewer revisions than nonimpregnated devices even in the challenging replacement surgery setting. At almost 7 years of followup of more than 11,000 replacement implant recipients secondary revision due to infection was noted in 2.5% of 9,300 men with an M/R impregnated device vs 3.7% of 1,764 with a nonimpregnated device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the organisms are suppressed by the antibiotics in M/R impregnated devices and must be recognized and cautiously monitored in clinical practice, and assessed in future research. 13,14,18,21,22 To our knowledge the strength of the data used for analysis provides the most tangible evidence to date that M/R impregnated implants are enhanced and require fewer revisions than nonimpregnated devices even in the challenging replacement surgery setting. At almost 7 years of followup of more than 11,000 replacement implant recipients secondary revision due to infection was noted in 2.5% of 9,300 men with an M/R impregnated device vs 3.7% of 1,764 with a nonimpregnated device.…”
Section: Discussionmentioning
confidence: 99%
“…17 In 2011 Kava et al reported the outcome of a prospective study in 189 patients, of whom 70 underwent implant removal/replacement/rerouting due to mechanical malfunction or extrusion. 18 Infection developed in 5 patients (7.1%) after revision, although only 57% of the procedures included washout and only approximately 70% of implants were coated or impregnated with antibiotics. In each study the infection risk associated with revision of a malfunctioning device was no greater than in the concurrent cohorts of primary implant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, several recent reports of infection in coated devices demonstrated that bacterial species differ in coated implants, ie S. aureus and Enterobacter aerogenes. 9 After these species gain access, the bacteria attempt to adhere to the device surface and produce a protective layer of extracellular polymers, termed biofilm. 10 This layer has 2 effects.…”
mentioning
confidence: 99%
“…Interestingly, our fourth case features an entirely asymptomatic reservoir that was colonized with bacteria. This is not surprising, as 10–80% of implants undergoing revision surgery for mechanical failure harbor asymptomatic bacteria within the peri‐implant space, which may increase the risk of infection associated with revision surgery .…”
Section: Discussionmentioning
confidence: 99%